THE PEDAGOGICAL AND PSYCHOLOGICAL ASPECTS OF PREPARING FUTURE CHEMISTRY TEACHERS FOR INTERNATIONAL ASSESSMENT STUDIES - Tilyabov Maxsudjon Umurzokovich (Research Focus International Scientific Journal, 2025)
This article discusses the pedagogical and psychological aspects of preparing future chemistry teachers for international assessment studies. It highlights the scientific research of scholars and their pedagogical-psychological perspectives. Additionally, the works of authors who have conducted research on developing competencies for international assessments, as well as those who have created educational manuals and didactic materials in this area, are analyzed. The research findings and the methodological section mainly present an analytical review of scholars’ scientific works.